1994
DOI: 10.1016/0014-5793(94)80559-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis is operative in amphibian oocytes

Abstract: It is generally accepted that in frog full-grown oocytes glycolysis is absent and that carbon metabolic flux is largely directed to glycogen synthesis. Use of an anion exchange pellicular resin for analytical resolution of intermediates in perchloric acid extracts of oocytes has allowed us to observe the formation of labelled lactate after microinjection of [u-i4C]glucose. Further, formation of ["P]ATP was observed after microinjection of 32P-labelled glucose-6-P, fructose-6-P or fructose-1,6-b&P, either in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Separation and identification of metabolic intermediates was as described in [3], except that the CarboPac PA1 column was equilibrated with 90 % solution A (100 mM NaOH) and 10 % solution B (1 M sodium acetate\100 mM NaOH) and eluted at a flow rate of 0.5 ml\min with the following gradient : T ! l 10 % ; T #!…”
Section: Separation Of Metabolic Intermediates By Ion-exchange Chromamentioning
confidence: 99%
See 2 more Smart Citations
“…Separation and identification of metabolic intermediates was as described in [3], except that the CarboPac PA1 column was equilibrated with 90 % solution A (100 mM NaOH) and 10 % solution B (1 M sodium acetate\100 mM NaOH) and eluted at a flow rate of 0.5 ml\min with the following gradient : T ! l 10 % ; T #!…”
Section: Separation Of Metabolic Intermediates By Ion-exchange Chromamentioning
confidence: 99%
“…Labelled glucose (microinjected or present in the incubation medium) is readily incorporated into glycogen and, to a minor extent, released as CO # through the pentose phosphate pathway only, since [6-"%C]glucose does not produce "%CO # [1,2]. All enzymes of glucose utilization are present in oocyte homogenates [1], including phosphofructokinase [3] and fructose-1,6bisphosphatase [4], previously thought to be absent from these cells [5]. A recent paper from our laboratory [3] reported that a significant amount of carbon from [U-"%C]glucose was found, after 5 min incubation, in lactate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycolysis is operative in grown amphibian oocytes [1], although glucose injected into the cells is mostly utilized for glycogen synthesis [2, 3]. Glucose incorporation into the polysaccharide occurs preferentially by the so called indirect pathway, which involves prior degradation of glucose into three carbon compounds which then by gluconeogenesis, regenerate hexoses‐P and UDP‐glucose, the proximate glycogen precursor [4].…”
Section: Introductionmentioning
confidence: 99%
“…1, left). Glycolytic intermediates cannot be detected at those early times, i.e., glucose breakdown proceeds at a very low steady-state of intermediates (7), a fact that suggests channelling of the pathway. Then, labeled glycogen begins to accumulate and hexoses-P can be detected.…”
Section: Two Pathways For Glycogen Synthesis In Frog Oocytesmentioning
confidence: 99%